(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The management system in society has been in a process of constant change and improvement. In this process, the personal qualities and leadership skills of individuals performing leadership functions are of great importance. In the modern world, women leaders play a major role in shaping transformations in the economic, social and cultural spheres of society. This article analyzes the contribution of women leaders to the management system, their specifics and important aspects in managing transformation processes.